Možnosti využití šedých vod - Bogáňová, Ida Antonie (Vysoké učení technické v Brně. Fakulta stavební, 2016)
Šedá voda je odpadní voda z umyvadel, sprch, van, kuchyňských dřezů, myček a praček. Jejich úpravou je možné získat tzv. vodu bílou, kterou lze využít např. na splachování toalet a pisoárů, zalévání zeleně nebo k úklidu. Předmětem této diplomové práce je uvést možnosti využití šedých vod. V první části této práce bude vypracována rešerše k danému tématu. V následující kapitole budou uvedeny příklady možností využívání šedých vod. Praktická část by měla spočívat v návrhu systému úpravy šedých vod v konkrétním objektu.

Greywater is waste water from washbasins, showers, baths, kitchen sinks, dishwashers and washing machines. This can be treated to gain so-called white water, which can for example be used for flushing toilets and urinals, watering greenery or for cleaning. The subject of this diploma thesis is to state the possibilities for utilisation of greywater. In the first part of this thesis, research will be elaborated on the given topic. In the following chapters, I would like to state examples of the possibilities for utilisation of greywater. The practical part should consist of design of a system for treatment of greywater in a specific building.
Possibilities of using gray waters
Keywords: Šedá voda; bílá voda; vnitřní kanalizace; vnitřní vodovod; membránový modul; vodné; stočné.; Greywater; white water; sanitary plumbing; internal water mains; membrane module; water rates; sewage rates.